Similar progression of carotid intima–media thickness in 7-year surveillance of patients with mild SLE and controls, but this progression is still promoted by dyslipidaemia, lower HDL levels, hypertension, history of lupus nephritis and a higher prednisolone usage in patients - Thomas Gustafsson; Sofia Ajeganova; Linnea Lindberg; Ingiäld Hafström; Johan Frostegård (Lupus Science and Medicine)
Objective To compare progression of subclinical atherosclerosis and factors promoting it in patients with SLE and controls.Methods Consecutive patients with SLE and age-matched, sex-matched population controls from the SLEVIC cohort were assessed at inclusion and after 7 years with standardised data collection and carotid ultrasound. Effect of risk factors on carotid intima–media thickness (cIMT) progression was examined with adjusted linear mixed models.Results A total of 77 patients and 74 controls, 68% and 61% of the original cohort, completed follow-up. The patients were (mean) 47 years old, 90% were women, and controls were 51 years old, 92% women. Patients had disease duration of (mean) 11 years, mild disease activity and low severity at both assessments. Baseline cIMT did not differ between the groups. An average absolute cIMT progression was 0.009 mm/year in patients and 0.011 mm/year in controls, intergroup difference p=0.9.Of factors at inclusion, dyslipidaemia, lower levels of high-density lipoprotein (HDL) and carotid plaque in patients and controls, and higher systolic blood pressure, total cholesterol:HDL and LDL:HDL ratios and triglycerides in patients were associated with cIMT progression. Of factors at follow-up, hypertension and blood lipids in patients and HDL in controls were significantly associated with cIMT progression. History of lupus nephritis and a higher average dose of prednisolone used since diagnosis were associated with cIMT progression in patients. Associations of risk factors with cIMT progression were stronger in presence of plaques.Conclusion We observed a statistically comparable progression of cIMT in patients with mild SLE and controls over 7 years, which implies that progression of subclinical atherosclerosis in some patients with SLE could follow that of the general population. Traditional cardiovascular (CV) risk factors, history of lupus nephritis and higher use of corticosteroids promote cIMT progression in SLE. Detection of carotid plaque may add to CV risk stratification.